KAJIAN ETNOBOTANI BIDANG KOSMETIK DI KAMPUNG SAMBIKITING SERANG BANTEN - Amaliah, Ratu Zulfi; Pramudita, Wida Putri; Yuliasari, Arsyida; Fitriana, Desi Eka Nur (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2023)
The fact that local people use plants as materials for their daily needs, be it medicine, art, cosmetics, etc. is called ethnobotany. Ethnobotany is engaged in various fields, one of which is cosmetic ethnobotany. In ancient times cosmetic products have become an important part of people's lives.Its use is widespread for both beauty and health purposes. The use of plants in Sambikiting Village, Sambilawang Village, Waringinkurung District is very diverse in the cosmetic field. Plants that are often used by the community are Magnoiophyta plants, including coconut, guava shoots, betel leaves, and rice.